2016
DOI: 10.1111/aos.13143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CC‐cytokine ligand 2 and complementary factor H Y402H polymorphisms and their interactional association with age‐related macular degeneration

Abstract: Complement factor H Y402H polymorphism is strongly associated with advanced type AMD. Although this study revealed no association of CCL2-2518 with AMD, the risk effect of CFH genotypes was only visible in the presence of AA genotype of CCL2-2518. AG genotype of CCL2-2518 in combination with TT genotype of CFH Y402H showed significant protective effect against AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…It should be bear in mind that the other genes of the complement system including C3 (rs2230199), CFI (rs141853578), and CFH (rs2274700, rs3753395, rs800292, and rs1061170) had previously studied in this population have shown their association with the disease [17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be bear in mind that the other genes of the complement system including C3 (rs2230199), CFI (rs141853578), and CFH (rs2274700, rs3753395, rs800292, and rs1061170) had previously studied in this population have shown their association with the disease [17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is the main risk factor and recent evidence indicates the involvement of several environmental factors such as smoking in the pathogenesis of this disease [ 2 ]. Based on the pathological features of AMD, the role of dysregulation of inflammatory and immune responses in the etiology of the disease has been demonstrated [ 3 6 ]. As inflammation has the main role in the pathogenesis of AMD, dysfunction of the complement system is proposed to cause choroidal neovascularization [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…; Bonyadi et al. ). As a subtype of AMD, RPD is associated with high risk of progression to advanced AMD (Arnold et al.…”
Section: Introductionmentioning
confidence: 97%
“…The CFH Y402H, mapped on chromosome 1q31 and ARMS2 A69S, mapped on chromosome 10q26, are well-established risk factors for AMD (Weeks et al 2004;Rivera et al 2005;Bonyadi et al 2016). As a subtype of AMD, RPD is associated with high risk of progression to advanced AMD (Arnold et al 1995;Zweifel et al 2010a,b;Pumariega et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using online search databases with keywords including "polymorphism", "age-related macular degeneration", and "meta-analysis", I summarized the findings from the latest published meta-analysis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] as shown in Figure 1. Moreover, in this short communication additional meta-analysis of TNFα, CCL-2, MMP3, MMP7, MMP9, and TIMP2 were also included [19][20][21][22][23][24][25][26][27][28][29] . It was shown that a protective effect of TNFα -863A carrier (A vs C, OR = 0.67, P = 0.007; AA+CA vs CC, OR = 0.58, P = 0.001; CA vs AA+CC, OR = 0.55, P = 0.001; and CA vs CC, OR = 0.54, P = 0.001, Figure 2A-D) and TIMP2 -418C carrier (GC vs CC+GG, OR = 0.54, P = 0.018; and GC vs GG, OR = 0.56, P = 0.046, Figure 2E,F) to the development of AMD.…”
mentioning
confidence: 99%